Discriminating Catch Composition and Fishing Modes in an Artisanal Multispecies Fishery - Purcell, Steven W.; Fraser, Nicola J.; Tagica, Sailasa; Lalavanua, Watisoni; Ceccarelli, Daniela M. (Frontiers in Marine Science, 2018)
Many small-scale fisheries are multi-species, and the catch composition can vary according to available habitats, fishing modes and fisher groups. Here, we applied novel approaches for understanding the factors affecting differences in catch composition among fishers, which should be useful for planning regulatory measures and fishery development initiatives. Interviews with 235 artisanal fishers in Fiji were used to analyse how fishers’ catch composition of 22 species of sea cucumbers varied across geographic scales (locations and villages within locations), genders and fishing modes. Venn diagrams illustrated that gleaning and SCUBA diving were practised to varying extents among locations and genders, whereas fishers used breath-hold diving more uniformly across the fishery. Segmented bubble plots revealed spatial variations in catch composition across the fishery. A PERMANOVA analysis found that species catch composition varied most across both geographic scales and, secondarily, among fishing modes and between genders. Gendered differences in catch composition were variable from one village to another, and so should not be generalised. SIMPER analyses showed that gleaners and SCUBA divers caught significantly different suites of sea cucumber species. Species threatened with extinction were among those typifying catches of SCUBA divers. Our novel graphical techniques are useful for visualising fishing modes and catches across other fisheries. Artisanal fisheries may exhibit strong heterogeneity in catch at multiple spatial scales. Planning of regulatory measures that limit certain fishing modes or species should take into account the likely differential impacts on different fishing communities and genders.